Market Orientation and Hotel Industry: Developing a Measurement Model - Sampaio, Carlos Alberto Fernandes (2018)
Submitted by Ricardo Rodrigues (rjagr@ubi.pt) on 2018-11-30T11:56:52Z No. of bitstreams: 1 Market Orientation and Hotel Industry – Developing a Measurement Model.pdf: 449357 bytes, checksum: 6f9f4bf2a706d8ba12985f3231d30ff9 (MD5)